The role of global air pollution in aging and disease reading smoke signals - Finch, Caleb 1939- (Elsevier, Academic Press, an imprint of Elsevier, 2018)
Global Air Pollution in Aging: Reading Smoke Signals is a complete reference connecting environmental pollution research to the human aging process. Since 1800, lifespans have more than doubled as infections declined and medicine improved. But the 20th century introduced a new global scourge of air pollution from fossil fuels with the potential to damage arteries, hearts and lungs that has been related to chronic exposure of air pollution from fossil fuels. Risk areas of study include childhood obesity, brain damage associated with air pollution, increased risk for autism in children and dementia in older adults